Safety evaluation of the food enzyme rennet containing chymosin and pepsin A from the abomasum of suckling goats, lambs and calves - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal, 2022)
Abstract The food enzyme containing chymosin (EC 3.4.23.4) and pepsin A (EC 3.4.23.1) is prepared from the abomasum of suckling goats, lambs and calves by Laboratoires Abia. The food enzyme is intended to be used in milk processing for cheese production. As no concerns arise from the animal source of the food enzyme or from its manufacture, and based on the history of safe use and consumption, the Panel considered that toxicological data and the estimation of dietary exposure were not required. On the basis of literature data, the Panel considered that, under the intended conditions of use, the risk of allergic reactions by dietary exposure could not be excluded, but the likelihood for this to occur was considered low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.